PENGARUH LOVE AFFIRMATION AYAH TERHADAP KEMAMPUAN SOSIAL EMOSIONAL ANAK DI TAMAN KANAK – KANAK NEGERI PEMBINA 1 SURABAYA - Amalia Ihza Nurria Syah Yunda; Muhammad Reza; Dewi Komalasari; Wulan Patria Saroinsong (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of fathers' love affirmations on the social-emotional abilities of early childhood children at Pembina 1 State Kindergarten, Surabaya. The family is the primary environment for children to gain early emotional experiences, where the father's role plays an important role in building emotional closeness and character development. However, the phenomenon of suboptimal father involvement in parenting is still common, resulting in the fulfillment of children's emotional needs, especially through love affirmations, not being fully met. This study aims to determine the effect of fathers' love affirmations on the social-emotional abilities of early childhood children. The research method used is a quantitative approach with a correlational research design. The subjects of the study were early childhood children at Pembina 1 State Kindergarten, Surabaya, with data collection techniques using questionnaires given to parents and observation sheets for children's social-emotional development. The data obtained were analyzed using statistical analysis techniques through regression tests to determine the magnitude of the influence of fathers' love affirmations on children's social-emotional abilities. The results showed that fathers' love affirmations have an influence on children's social-emotional abilities, although their contribution is in the low category. These findings suggest that fathers' expressions of affection through affirming words, attention, time spent together, and positive actions continue to play a role in supporting children's social and emotional development, such as the ability to manage emotions, develop self-confidence, and interact with the social environment. Therefore, this study emphasizes the importance of father involvement in parenting through the consistent application of love affirmations as an effort to optimally support the social and emotional development of early childhood.